Barriers and facilitators of integrated hepatitis B, C, and HIV screening among pregnant mothers and newborns attending maternal and newborn clinics in Koboko District, Uganda: a qualitative inquiry of providers’ perspective - John Bosco Alege; John Paul Oyore; Rose Clarke Nanyonga; Philippa Musoke; Alloys S. S. Orago (BMC Infectious Diseases)
Abstract Background HIV and HBV remain significant public health challenges characterized by high prevalence, morbidity, and mortality, especially among women of reproductive age in Uganda. Patients with HBV do not receive routine counselling and education, and there are limited resources for laboratory investigation coupled with a high loss to follow-up. This study set out to assess barriers and facilitators of integrated viral hepatitis B C and HIV care model to optimize screening uptake among mothers and newborns at health facilities in Koboko District, west Nile sub-region, Uganda. Methods An exploratory qualitative descriptive study that used an inducted and deductive thematic analysis approach was used at Health Centre III (HC IIIs) level in an institutional setting. The study participants (Key Informants) were both clinical and administrative health workers involved in the delivery of Hepatitis B, C, and HIV services. Data was audio recorded using a recording device and then transcribed after all interviews were conducted. Data was then analyzed using thematic analysis. Results The facilitators of integration were established to be; High burden of hepatitis B infection, team spirit by the health workers, reduced long waiting time, availability of medical products such as HBV and HCV test kits, integration of HBV and HIV into Health Management Information System (HMIS) 2 data collection tools and availability of support from implementing partners such as Infectious Disease Institute which offered mentorship and training on integration and support supervision. While the barriers included; Knowledge gaps among healthcare workers, limited Health education, Language barriers that made communication between health workers and mothers difficult, constant stock out of test HBV kits, no supplies for HCV kits, and inadequate staffing. Conclusion The need to reduce ‘lost opportunity’ by pregnant mothers in accessing HBV, HVC, and HIV at one point of care underscores the necessity of integrated care. Strong team spirit, reducing patient waiting times, and enhancing the incorporation of HBV and HIV into the HMIS2 form are essential steps. Additionally, support from implementing partners like IDI, is pivotal. Several barriers impede effective integration. Addressing knowledge gaps among healthcare workers, providing transportation, minimizing language barriers during health education, addressing insufficient human resources, and preventing frequent stock-outs of test kits for HBV and HCV are crucial to enhancing the effectiveness and efficiency of integration.